2016
DOI: 10.32870/lv.v5i43.5837
|View full text |Cite
|
Sign up to set email alerts
|

Aportes de la investigación social en salud: la importancia de la perspectiva de género en la comprensión de la enfermedad coronaria

Abstract: This paper discusses the contributions made by social sciences, particularly from gender and socio cultural studies regarding coronary diseases (CD), specifically for women. It is assumed that the interpretation models for these perspectives enable the integral study of the health-diseasecare process for CD, they also generate knowledge about gender inequality in health; visualizing risks beyond biological differences; to identify their self-perception and which are the experiences along the CD process, as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
1
0
2
Order By: Relevance
“…Those speaking an indigenous language and living in overcrowded households or in rural areas were found to be the least knowledgeable. Previous research has shown that partial or complete unawareness of sexual and reproductive rights prevents people from enjoying the full benefits of citizenship [ 29 , 30 ]. In addition, as has been observed in other countries [ 31 ], lacking awareness of the right to information and to SRH services carries a whole set of negative consequences for the health of adolescents, often culminating in domestic violence.…”
Section: Discussionmentioning
confidence: 99%
“…Those speaking an indigenous language and living in overcrowded households or in rural areas were found to be the least knowledgeable. Previous research has shown that partial or complete unawareness of sexual and reproductive rights prevents people from enjoying the full benefits of citizenship [ 29 , 30 ]. In addition, as has been observed in other countries [ 31 ], lacking awareness of the right to information and to SRH services carries a whole set of negative consequences for the health of adolescents, often culminating in domestic violence.…”
Section: Discussionmentioning
confidence: 99%
“…Ambos estadíos se caracterizan por la asociación con el amor, el trabajo, la salud, por la formación, educación, creatividad, bienestar y cuidado, confianza, esperanza (amor, familia, profesión, religión), Investigación 8 Revista Uruguaya de Enfermería, 2023;18(2):e2023v18n2a1 DOI: 10.33517/rue2023v18n2a1 -eISSN: 2301-0371 autonomía y libertad. Cada estadío está marcado por una crisis de carácter psicosocial, donde se aprecian los patrones de comportamiento acordes a cada edad (10) (11) (12) . Durante el período fértil las mujeres tienen cierta protección contra las enfermedades cardíacas debido a los estrógenos.…”
Section: Para Este Estudio Se Tuvo En Cuenta Los Factores Psicosocial...unclassified
“…En las últimas décadas, muchos investigadores han tratado de analizar las distintas actitudes de los profesionales sanitarios, específicamente en lo que se refiere a la toma de decisiones para la prescripción de medicamentos según el sexo del paciente. Esto mismo se muestra en los estudios realizados sobre el diagnóstico y tratamiento de patologías como las enfermedades coronarias, ya que tradicionalmente son asociadas a los hombres (63,64). Tal y como señala Blech (51), a igualdad de patología, muchas mujeres son excluidas del procedimiento habitual, con el riesgo de no recibir un tratamiento adecuado para una enfermedad o problema cardiovascular.…”
Section: Sesgos De Género Y Salud Mentalunclassified